Fifteen grandparents stories (Sunway University. Dept. of Performance & Media, 2007)
Fifteen stories about their grandparents as told to the students of the Diploma in Performing Arts November 2007. Contents:1. Night in the jungle. - 2. Spy no. 3.- 3. Bullets.- 4. Wrong place at the right time. - 5.The luckiest guy. - 6.Don't go looking for trouble. -7. Under the umbrella. - 8. A tale of ICs and bicycles. -9. Yong Che. - 10. Sole survivor. - 11. Budi terkenang. - 12. Injustice. - 13. An old fart's dream. - 14. TimBuctu. - 15. Long Awaited moment.